RUPTURED IDIOPATHIC SPLENIC ARTERY PSEUDOANEURYSM — A CASE REPORT AND LITERATURE REVIEW - Coelho, Andreia (2019)
Introduction: Splenic artery pseudoaneurysms (SAP) represent a rare clinical entity typically caused by sequelae of pancreatitis or abdominal trauma. Unprovoked, spontaneous SAP are exceedingly rare, with only two other case reports in the literature up to date. In this paper we pretend to present a case of a ruptured idiopathic SAP successfully treated endovascularly.Methods: Relevant medical data were collected from hospital database.Results: The patient is a 75-year-old male with no past history of pancreatitis, abdominal trauma or abdominal surgery. He was admitted in the emergency department with thoracalgia with interscapular irradiation with few hours of evolution. He referred food intolerance with vomiting for approximately 7 days.In the diagnostic work-up, a computed tomography angiogram (CTA) was performed and revealed a previously unknown voluminous hiatus hernia and a ruptured 25 mm SAP with active bleeding into a 104x98 mm perigastric collection in the left hypochondrium extending to the thorax, a 34 mm peri-pancreatic and a 35 mm pararenal collection. Urgent treatment was planned in the angiography suite, and after selective catheterization of the splenic artery, pseudoaneurysm origin was identified and embolized both proximally and distally with coils. The end result angiogram was apparently successful. CTA was repeated and revealed complete embolization of the pseudoaneurysm, with no evidence of bleeding. Peri-aneurysmaticcollections remained unchanged in size and splenic infarction was evident in 50% of parenchyma. He was discharged 10 days after the initial procedure.Conclusions: Endovascular surgery seems a good option for SAP even in rupture, with good short-term results. In this case, it was admitted that it could be a bridge to open surgery with aneurysmectomy and splenectomy. However, given the good clinical recovery post-embolization, no further surgery was considered. Nowadays there is little consensus on follow-up, and long term results are largely unknown.